Magical Moments in Anaheim! 2016 Annual American Academy of Optometry Meeting - Dalton, Kristine; Bitton, Etty (Canadian Journal of Optometry, 2018)
There seemed to be magic in the air at the 2016 Annual American Academy of Optometry meeting in Anaheim, California. The meeting once again set an attendance record of 7,720 attendees representing 53 nations. A total of 315 Canadians made the trip south, including 81 students from Quebec (Figure 1), 32 students from Waterloo [...]